Start performance and its relation to competition times in Paralympic swimmers - Clephas, C.; Stergiou,P.; Katz, L. (Journal of Human Sport & Exercise, 2019)
The purpose of this study was to investigate the relationship between the variability of the 100m freestyle final race time to start performance in a population of Paralympic swimmers using the coefficient of variation (CV). A secondary purpose of study was to investigate the correlation between start performance and competition results in this population of athletes. A total of 321 data points were collected on start performances and 231 data points were collected from competition results. It was found that there was a within-athlete CV in final times of 2.6% and a within-athlete CV in start performances of 18.2%. These two parameters were moderately correlated having an r2 of 0.57. The athletes improved their performances across five-consecutive seasons by 6.4%. In addition, it was found that a strong correlation existed between the 5m start time compared to the final race time in the 100m freestyle (r2=0.78). The results showed that the variability of start performance was moderately correlated to the variability of the final times and there was a strong correlation between start performance and competition results.